Critical Thinking in Science Learning Research Tren From 2014-2024: A Systematic Literature Review - Irfan Akbar; Sulistyo Saputro; Mohammad Masykuri (Jurnal Penelitian Pendidikan IPA, 2024)
Critical thinking involves identifying a problem by drawing on experience from past issues, finding relationships between these issues, and solving them in different contexts. This study aims to analyze research trends on critical thinking in science learning from 2014 to 2024. The research method is descriptive and analytical, using the PRISMA research procedure. The data comprises articles from the Scopus and Google Scholar databases, accessed with the help of Publish or Perish (PoP) software. The analyzed data includes publication year, author density, journal density, and highly cited articles. Data analysis is conducted using bibliometric analysis, supported by VOSViewer software. The findings indicate a positive trend in publications from 2014 to 2024, with slight fluctuations before a significant decline after 2021. *Wilujeng* is identified as the most prolific author, while the *Journal of Physics: Conference Series* is the journal with the most articles published on this topic. The article by Blair, Clancy published in 2014 holds the highest citation count, with 300 citations. Over the past decade, Indonesia has dominated publications in this area, accounting for 74.55% of the total